2017
DOI: 10.1016/j.marpolbul.2017.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of common polymer ropes in a sublittoral marine environment

Abstract: Contamination by microplastic particles and fibres has been observed in sediment and animals sampled from the Firth of Clyde, West Scotland. In addition to microplastics released during clothes washing, a probable source is polymer ropes in abandoned, lost and discarded fishing and recreational sailing gear. The fragmentation of polypropylene, polyethylene, and nylon exposed to benthic conditions at 10m depth over 12months was monitored using changes in weight and tensile properties. Water temperature and ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(52 citation statements)
references
References 38 publications
(49 reference statements)
3
42
0
Order By: Relevance
“…All these polymers are susceptible to photo-initiated oxidative degradation, which is believed to be their most important abiotic degradation pathway in aerobic outdoor environments. This degradation pathway consists of a complex sequential multi-step process where initially chemical bonds in the main polymer chain are broken down by light, by heat or by a combination of both to produce a free radical formation [3,4]. Polymer radicals react with oxygen and form a peroxy-radical species.…”
Section: Sources Degradation Processes Detection Of Plastic Debris mentioning
confidence: 99%
See 2 more Smart Citations
“…All these polymers are susceptible to photo-initiated oxidative degradation, which is believed to be their most important abiotic degradation pathway in aerobic outdoor environments. This degradation pathway consists of a complex sequential multi-step process where initially chemical bonds in the main polymer chain are broken down by light, by heat or by a combination of both to produce a free radical formation [3,4]. Polymer radicals react with oxygen and form a peroxy-radical species.…”
Section: Sources Degradation Processes Detection Of Plastic Debris mentioning
confidence: 99%
“…Different density solutions have been used including NaCl, ZnCl 2 , NaI and more recently 3Na 2 WO 4 9WO 3 H 2 O to obtain dense floating solutions [28,29]. However, it has been shown that simple density fractionations will not succeed in separating organic matter from plastic materials in sediments because most of the OM show densities between 1.0 and 1.4 g/cm 3 , similar to that of several environmentally recurring plastic types like PET, PP, PE and Nylon. Sufficient removal of OM without destroying small plastic polymers is challenging because large parts of OM are refractory.…”
Section: Extracting Microplastics From Environmental Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional groups, like esters, amides, carbonates, and urethanes, allow much faster surface erosion via enzymatic hydrolysis and abiotic hydrolysis than plastics without functional groups, such as PE and polystyrene (PS). Although Nylon degradation is slower than polyesters, biodegradation of nylon rope submerged in the ocean was 1% per month over a 12-month period 22 .…”
mentioning
confidence: 96%
“…Nowadays, some researchers find that microplastic particles even exist in people's daily drinking water. Therefore, the researchers gradually use biodegradable polymer materials to replace common polymer materials for reducing environmental pollution …”
Section: Introductionmentioning
confidence: 99%